High precision visual localization method of UAV based on feature matching - Xue, Bayang; Yang, Zhong; Liao, Luwei; Zhang, Chi; Xu, Hao; Zhang, Qiuyan (Frontiers in Computational Neuroscience, 2022)
In this paper, the precision hovering problem of UAV operation is studied. Aiming at the diversity and complexity of UAV operating environment, a high-precision visual positioning and orientation method based on image feature matching was proposed. The image feature matching based on the improved AKAZE algorithm is realized, and the optimal matching point pair screening method based on the fusion of Hamming distance and matching line Angle is innovatively proposed, which greatly improves the robustness of the algorithm without affecting the performance of the algorithm. The real-time image is matched with the benchmark image for image feature matching. By reducing the deviation of image feature, the pose state correction of UAV hovering is achieved, and the precision hovering of UAV is realized. Both simulation and real UAV test verify the effectiveness of the proposed UAV high-precision visual positioning and orientation method.